Extracellular Vesicle-Mediated Processes in Cardiovascular Diseases - Rory R. Koenen; Elena Aikawa (Frontiers Media SA, 2018)
It is long known that many cells can shed extracellular vesicles, small membrane-enclosed cell fragments. Although the existence of extracellular vesicles has been recognized for many years, researchers are only beginning to understand their physiologic significance. Several recent studies have demonstrated that extracellular vesicles released from cells serve as a mode of cellular communication. They can carry diverse molecular payload (e.g. nucleic acids, bioactive lipids and proteins) to distal organs and recipient cells. Extracellular vesicles can be classified into three major groups: exosomes, microvesicles, and apoptotic bodies. All these types of extracellular vesicles can be found in a variety of biologic specimen and their numbers, distribution and composition may serve as biomarkers for various disorders, including cardiovascular disease. Although extracellular vesicle-mediated processes are currently best characterized in the fields of cancer biology and neurobiology, evidence is accumulating that extracellular vesicles play a key role in the pathophysiology of diabetes, thrombosis, inflammation and cardiovascular calcification. In this Research Topic, we invited review and methodological articles that advance our understanding of extracellular vesicle-related processes in vascular biology.
English
Keywords: Angiogenesis; Atherosclerosis; Extracellular vesicles; Calcification; Biomarkers; Cardiovascular disease; Inflammation; Exosomes; Platelets; Heart valve